2010
DOI: 10.1038/ejhg.2010.203
|View full text |Cite
|
Sign up to set email alerts
|

On the origin and diffusion of BRCA1 c.5266dupC (5382insC) in European populations

Abstract: The BRCA1 mutation c.5266dupC was originally described as a founder mutation in the Ashkenazi Jewish (AJ) population. However, this mutation is also present at appreciable frequency in several European countries, which raises intriguing questions about the origins of the mutation. We genotyped 245 carrier families from 14 different population groups (Russian, Latvian, Ukrainian, Czech, Slovak, Polish, Danish, Dutch, French, German, Italian, Greek, Brazilian and AJ) for seven microsatellite markers and confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 28 publications
5
78
1
5
Order By: Relevance
“…The BRCA1 c.5266dupC mutation (also known as 5382insC) was the most prevalent mutation identified in this study. This Ashkenazi Jewish founder mutation [34,35] has been described in Dutch, Russian, French and many other populations, and a recent study showed that 245 carriers from 14 different populations presented the same haplotype, suggesting a single founder origin [36]. Indeed, this is one of the most common mutations identified in Brazilian patients to date [22,24,25], and Gomes et al [22] found 5382insC in 56% of all BRCA mutation carriers, and a very similar frequency (57%) was described by Lourenço et al [37].…”
Section: Resultsmentioning
confidence: 98%
“…The BRCA1 c.5266dupC mutation (also known as 5382insC) was the most prevalent mutation identified in this study. This Ashkenazi Jewish founder mutation [34,35] has been described in Dutch, Russian, French and many other populations, and a recent study showed that 245 carriers from 14 different populations presented the same haplotype, suggesting a single founder origin [36]. Indeed, this is one of the most common mutations identified in Brazilian patients to date [22,24,25], and Gomes et al [22] found 5382insC in 56% of all BRCA mutation carriers, and a very similar frequency (57%) was described by Lourenço et al [37].…”
Section: Resultsmentioning
confidence: 98%
“…To estimate the age of the mutation (or, more precisely, the number of generations as the most recent common ancestor (MRCA) of the 185delAG carriers), we used the method that was first used to estimate the age of several BRCA1 mutations, including the mutation that is the focus of the present study, 185delAG* BRCA1, 18 and then extended and applied to BRCA2 mutations, 28 and which has been used in several other similar studies, most recently in an analysis of the mutation BRCA1*c.5266dupC (5382insC). 29 This method uses maximum likelihood and allows for both recombination and mutational events at the marker loci as means of altering a presumed ancestral haplotype. Phased haplotypes were used if these could be inferred from available family data; otherwise, all possible haplotypes were constructed from multi locus genotype data and weighted according to their probability.…”
Section: Haplotype Construction and Age Of The Mutationmentioning
confidence: 99%
“…c.5266dupC mutation is the most prevalent BRCA1 mutation in Europe. It was originally described as founder mutation in the Ashkenazi Jewish population (Roa et al, 1996) but recently its origin was revealed as north European and it entered the Ashkenazi gene pool about 400-500 years ago (Hamel et al, 2011). BRCA1 mutations c.843_846delCTCA, c.1687C > T, c.5251C > T and c.676delT and BRCA2 mutation c.9371A > T were found in several nearby countries.…”
Section: Exonmentioning
confidence: 99%